(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The main qualitative and quantitative characteristics of phytoplankton in the studied areas of the Аmu-Bukhara channel and Tudakul reservoirs were studied and the occurrence of phytoplankton species of the Аmu-Bukhara channel and Tudakul reservoirs was determined. The largest total amount of phytoplankton in water samples from both reservoirs is Chlorophyta, while the largest phytoplankton biomass is Bacillariophyta and Bacillariophyta